2022
DOI: 10.3389/fphar.2022.911945
|View full text |Cite
|
Sign up to set email alerts
|

TRAF6 Suppresses the Development of Pulmonary Fibrosis by Attenuating the Activation of Fibroblasts

Abstract: Pulmonary fibrosis (PF) has a high mortality rate, and its pathogenesis is unknown. TNF receptor-associated factor 6 (TRAF6), a signal transducer for inflammatory signaling, plays crucial roles in the pathogenesis of immune diseases. However, its function in PF remains unknown. Herein, we demonstrated that lungs from mice with bleomycin (BLM)-induced PF were characterized by decreased expression of TRAF6 in lung fibroblasts. Enhancing TRAF6 expression protected mice from BLM-induced PF coupled with a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…TRIB3 was considered as a nutrient sensor and influenced energy metabolism by regulating intracellular signaling pathways, including AKT signaling cascade, MAPK pathways, and signaling pathways associated with β-cell apoptosis under heightened nutrient influx, insulin resistance, and elevated blood glucose levels [41][42][43]. TRIB3 has reported to act as a pivotal regulator of crucial cellular processes through its interactions with transcription factors such as CCAAT-enhancer-binding protein homologous protein (CHOP), peroxisome proliferator-activated receptor alpha (PPARα), and activating transcription factor 4 (ATF4), including glucose and lipid metabolism, adipocyte differentiation, autophagy, proteasomal degradation and apoptosis [12,40,44]. Recent report showed that compared to healthy subjects, TRIB3 level was significantly increased in plasma of diabetic patients, and high TRIB3 level was associated with fasting blood glucose and insulin resistance [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRIB3 was considered as a nutrient sensor and influenced energy metabolism by regulating intracellular signaling pathways, including AKT signaling cascade, MAPK pathways, and signaling pathways associated with β-cell apoptosis under heightened nutrient influx, insulin resistance, and elevated blood glucose levels [41][42][43]. TRIB3 has reported to act as a pivotal regulator of crucial cellular processes through its interactions with transcription factors such as CCAAT-enhancer-binding protein homologous protein (CHOP), peroxisome proliferator-activated receptor alpha (PPARα), and activating transcription factor 4 (ATF4), including glucose and lipid metabolism, adipocyte differentiation, autophagy, proteasomal degradation and apoptosis [12,40,44]. Recent report showed that compared to healthy subjects, TRIB3 level was significantly increased in plasma of diabetic patients, and high TRIB3 level was associated with fasting blood glucose and insulin resistance [45].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike traditional kinases, TRIB3 lacks the canonical adenosine triphosphate (ATP)-binding pocket and catalytic residues, leading to its classification as a pseudokinase. Instead of direct catalytic activity, TRIB3 functions as a molecular scaffold, orchestrating intricate interactions with various transcriptional mediators and signaling molecules [11][12][13]. The dysregulation of TRIB3 gene expression has been linked to several diseases, underscoring its importance in disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%